Prayer : experiencing awe and intimacy with God - Keller, Timothy J., 1950- (London : Hodder & Stoughton, 2014)
Tim Keller's Counterfeit Gods located our main personal and social problems in 'idols of the heart'; this is essentially its sequel, a very practical book on how to dismantle those idols and bring about deep and permanent changes in our character and behaviour. Tim begins by focusing on the means for growth. The basic tool is prayer, including reflective prayer that expands self-knowledge; meditative prayer that makes beliefs real to the heart and changes personal identity; confession that cleanses the conscience and reshapes the affections; and communal prayer and worship that seals us into a life-changing community which renews human relationships. After exploring these means for change, Tim examines the gospel virtues - the specific changes in character that these measures can produce, and ends with an incredibly practical, workable section on daily, weekly, and monthly spiritual exercises and practices. This is a book that will teach you to pray - and in doing so, will change your life.
Desiring prayer -- Understanding prayer -- Learning prayer -- Deepening prayer -- Doing prayer.
Includes bibliographical references.
Keywords: Prayer -- Christianity; Prayer -- Christianity